Influence of High Energy Diet and Polygenic Predisposition for Obesity on Postpartum Health in Rat Dams - Leuthardt, Andrea S.; Bayer, Julia; Monné Rodríguez, Josep M.; Boyle, Christina N. (Frontiers in Physiology, 2022)
It is estimated that 30% of pregnant women worldwide are overweight or obese, leading to adverse health effects for both mother and child. Women with obesity during pregnancy are at higher risk for developing both metabolic and mental disorders, such as diabetes and depression. Numerous studies have used rodent models of maternal obesity to understand its consequences on the offspring, yet characterization of changes in the dams is rare, and most rodent models rely solely on a high fat diet to induce maternal obesity, without regarding genetic propensity for obesity. Here we present the influence of both peripartum high energy diet (HE) and obesity-proneness on maternal health using selectively bred diet-resistant (DR) and diet-induced obese (DIO) rat dams. Outbred Sprague-Dawley rats were challenged with HE diet prior to mating and bred according to their propensity to gain weight. The original outbred breeding dams (F0) were maintained on low-fat chow during pregnancy and lactation. By comparison, the F1 dams consuming HE diet during pregnancy and lactation displayed higher gestational body weight gain (P < 0.01), and HE diet caused increased meal size and reduced meal frequency (P < 0.001). Sensitivity to the hormone amylin was preserved during pregnancy, regardless of diet. After several rounds of selective breeding, DIO and DR dams from generation F3 were provided chow or HE during pregnancy and lactation and assessed for their postpartum physiology and behaviors. We observed strong diet and phenotype effects on gestational weight gain, with DIO-HE dams gaining 119% more weight than DR-chow (P < 0.001). A high-resolution analysis of maternal behaviors did not detect main effects of diet or phenotype, but a subset of DIO dams showed delayed nursing behavior (P < 0.05). In generation F6/F7 dams, effects on gestational weight gain persisted (P < 0.01), and we observed a main effect of phenotype during a sucrose preference test (P < 0.05), with DIO-chow dams showing lower sucrose preference than DR controls (P < 0.05). Both DIO and DR dams consuming HE diet had hepatic steatosis (P < 0.001) and exhibited reduced leptin sensitivity in the arcuate nucleus (P < 0.001). These data demonstrate that both diet and genetic obesity-proneness have consequences on maternal health.